The The Role of the Quazi Courts in Family Dispute Resolution: Effectiveness and Limitations in the Sri Lankan Context - A.L.Nazeer Kany; SMM. Nafees (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
This study examines Sri Lanka’s Quazi court system and how it mediates family disputes. Beginning with an overview of the country’s mixed legal system, it highlights the application of Muslim personal law through specialized Quazi tribunals. The study assesses the strengths and weaknesses of Muslim Quazi courts, particularly within the MMDA framework. Although designed to provide more accessible and affordable family dispute resolution for the Muslim community, in practice the system raises concerns about effectiveness, legal certainty, and justice especially in relation to the protection of women’s rights. The article aims to analyze the role of Quazi Courts in resolving family disputes in Sri Lanka by evaluating their effectiveness, identifying structural and procedural limitations under the MMDA, and mapping their implications for gender equality and access to justice. The research adopts a qualitative socio-legal approach using secondary data through document review and doctrinal analysis. Sources include the MMDA, academic literature, institutional reports, and comparative studies on religion-based family courts within the context of legal pluralism. The data are analyzed through deductive thematic analysis to extract key themes such as operational weaknesses, gender disparities in the MMDA, impacts on women, and reform challenges. The findings indicate that Quazi Courts offer access-related advantages (low cost, opportunities for self-representation, and relatively rapid processing for simple cases), but their effectiveness is constrained by the lack of minimum qualifications and formal training for Quazis, irregular hearing schedules, inadequate infrastructure, weak oversight, and alleged corrupt practices. Normatively, several MMDA provisions are seen to reinforce gender inequality (child marriage, mandatory male guardianship, divorce procedures that disadvantage women, polygamy without strict scrutiny, and the absence of post-divorce property distribution rules), thereby weakening women’s protection and the overall quality of justice. This article recommends comprehensive MMDA reform (setting a minimum marriage age, strengthening women’s agency, ensuring equality in divorce procedures, regulating polygamy with strict safeguards, and establishing property division mechanisms), professionalizing and standardizing Quazi Courts (minimum qualifications, mandatory training, a code of ethics, effective supervision, and adequate court facilities).